Gradenigo’s Syndrome and Bacterial Meningitis in a Patient with a Petrous Apex Cholesterol Granuloma - Jacqueline Hodges; Julie Matsumoto; Nicholas Jaeger; Brian Wispelwey (Case Reports in Infectious Diseases)
Gradenigo’s syndrome (GS) classically involves a triad of ear pain due to acute or chronic otitis media (OM), facial or retro-orbital pain in the distribution of the trigeminal nerve, and an abducens nerve palsy. The simultaneous presentation of all three components has become less common in cases of GS reported in the literature, particularly in the era of antibiotics effective against typical organisms attributed to OM and petrous apicitis. In addition to infectious petrous apicitis arising directly from OM, more recent cases of GS are attributed to the compression of the same traversing cranial nerves in the presence of various expansile petrous apex (PA) lesions, both benign and malignant. We report a case of a 24-year-old male who presented initially with nausea, fever, photophobia, left-sided retro-orbital pain, and headache. He was diagnosed with bacterial meningitis by lumbar puncture and treated with empiric antibiotics, with CSF eventually revealing nontypeable Haemophilus influenzae. Several days into his course, he developed diplopia with leftward gaze. Brain imaging revealed an expansile, erosive PA cholesterol granuloma with associated contiguous dural and leptomeningeal enhancement. The patient improved with antibiotics and eventually underwent surgical intervention. This atypical presentation of GS with a rare complication of meningitis in the setting of a PA granuloma demonstrates the importance of early recognition of this syndrome, as well as consideration of added surgical intervention in patients with pre-existing petrous lesions at potentially higher risk of dangerous complications of GS.